Environment-Friendly Way... Keeping insects pests of tubers at bay - Harish, E. R.; Jayaprakas, C. A.; Korada, Rajasekhara Rao (Indian Horticulture, 2019)
With timely intervention and using various selective plant extracts and natural enemies, we can control pests of root and tuber crops effectively.